Physicochemical characterization of novel toothpaste from Caulerpa racemosa and Thunnus fish bone: Antibacterial potency against colonization of selected cariogenic-periodontal bacteria - Citra Fragrantia Theodorea; Fahrul Nurkolis; Erik Idrus; Timotius William Yusuf; Christopherous Diva Vivo; Dionysius Subali; Nurpudji Astuti Taslim; Alexander Patera Nugraha (Pensoft Publishers, 2024)
This study evaluated the physicochemical properties of toothpaste from combined Caulerpa racemosa and Thunnus fish bone (Toothpaste Caulerpa and Thunnus or TCT) and its antibacterial activity towards the colonization of selected cariogenic and periodontal bacterias. Four forms of toothpaste which contained C. racemosa extract and calcium carbonate or bone isolates of tuna and control (F1 (1.5:45); F2 (3:45); F3 (4.5:45); F4 (0:45)) were compared and analyzed for antioxidant activity (DPPH assay), organoleptic (sensory), homogeneity, viscosity, pH, and foamability. Antibacterial activity tests were conducted on Streptococcus mutans, Staphylococcus aureus, and Porphyromonas gingivalis. The antioxidant activity of the group's (F1, F2, F3, F4) p=0.0001 differed considerably (CI 95%). F3 was the most antioxidant-active formula, with 27.46 ± 3.09%. F3 also had good sensory tests, adequate homogeneity, optimal pH 7.64 ± 0.68, an increased viscosity level of 443.07 ± 0.12, and the least foam formations of 19.28 ± 0.07, all of which are significantly different (p<0.05) from other variations of TCT formulas. Interestingly, F3 has greater inhibition against the activity of selected bacterias. In conclusion, formula 3 (F3) is a recommended toothpaste, made from combined C. racemosa and Thunnus fish bone, and has promising physicochemical and antibacterial properties. A further clinical study is urgently needed.